Green human resource management practices to achieve an environmental sustainability in a manufacturing organisation - Jegathesan, Arumugam (2021)
There has been a recent rise in corporate understanding of the need of becoming green and using different environmental management strategies. A new capacity-based economy is emerging in the corporate world, ready to investigate the green economic aspects of business as the corporate world expands globally. GHRM, or Green Human Resource Management, has emerged as a critical economic strategy for major corporations whose HR departments actively participate in the movement to go green in the office. This research focusses on GHRM practices namely training development, employee engagement, and rewards system and its relationship with employee’s behaviour towards the environmental sustainability. The results proves that there is a strong relationship between training development and employee engagement toward employee’s behaviour towards the environmental sustainability. Meanwhile, there is positively moderate association between rewards system and employee’s behaviour towards the environmental sustainability. In nutshell, there is a significant relationship between green human resources management practices with employee’s behaviour towards the environmental sustainability among the employees in manufacturing firms in Kulim, Kedah. The study implication allows the employers and administrators of manufacturing firms to design their business strategies and goals that lead to clean environmental sustainability.